ARAH PENGEMBANGAN AGRIBISNIS BAWANG MERAH DI BANTUL (DEVELOPMENT OF IMPROVEMENT SHALLOT AGRIBUSINESS IN BANTUL REGENCY) - Suharyanta, Edy (Jurnal Ilmu-Ilmu Pertanian, 2006)
Shallot agribusiness is the uppermost agribusiness in Bantul Regency. This Fact pushes the desire of various party so that can be more developed. However the existence of various perception about different development agribusiness, like the improvement of wide harvest, farm productivity, variety diversification, the increasing of product quality. So that required to be re-studied how the opportunity of some efforts of the development and improvement. The study result indicates that the growth of wide area of shallot crop is increasing from year to year, but not linear increasing but fluctuate increasing. The plant wide area is increasing with the low increasing amount 1,3 ha/year. This case describes that the farmers from the outside of production centre are not easy to interested and change the plant pattern . But on the other side this condition has the positive implication, to minimize over supply of production in the market. Based on the mean productivity in 5 the last year hence the productivity of shallot in Bantul Regency still has opportunity to be improved.